2014
DOI: 10.1159/000363491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Brainstem Auditory Evoked Response at Different Click Rates between Preterm Babies after Neonatal Necrotizing Enterocolitis and Healthy Preterm Babies

Abstract: Background: Neonatal necrotizing enterocolitis (NEC) is associated with an increased incidence of poor neurodevelopment. The knowledge of underlying neurophysiology is very limited, and the influence of NEC on the preterm brainstem is very poorly understood. Objective: To assess the effect of NEC on the immature auditory brainstem by excluding any possible confounding effect of preterm birth. Methods: We recorded and analyzed brainstem auditory evoked response (BAER) at different click rates in preterm babies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Apgar at 5 min age, severe infection, respiratory distress syndrome (RDS), patent ductus arteriosus (PDA) closure, necrotising enterocolitis (NEC), bronchopulmonary dysplasia (BPD) and retinopathy were chosen based on their association with hearing loss in the literature. [14][15][16][17][18] Next, the clinical factors were divided into three different groups based on the nature of the variable. The clinical characteristic group included variables that describe the status of the infant as follows: sex, gestational age, Apgar score at 5 min and the age at the time of BAEP/BA.…”
Section: Discussionmentioning
confidence: 99%
“…Apgar at 5 min age, severe infection, respiratory distress syndrome (RDS), patent ductus arteriosus (PDA) closure, necrotising enterocolitis (NEC), bronchopulmonary dysplasia (BPD) and retinopathy were chosen based on their association with hearing loss in the literature. [14][15][16][17][18] Next, the clinical factors were divided into three different groups based on the nature of the variable. The clinical characteristic group included variables that describe the status of the infant as follows: sex, gestational age, Apgar score at 5 min and the age at the time of BAEP/BA.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we observed no differences in the incidence of retinopathy of prematurity in infants with NEC, suggesting that the type of blindness NEC survivors develop might occur through an independent mechanism, possibly via a cerebral injury. Hearing impairment in babies with NEC is proposed to result from impaired neural conduction in the brainstem auditory pathway, with NEC likely causing damage to myelination and synaptogenesis along the immature brainstem auditory pathway 82–84. Moreover, it has recently been reported that NEC survivors are more likely to develop long-term attention deficits that could lead to poorer educational outcomes and a need for specialised education 54.…”
Section: Discussionmentioning
confidence: 99%
“…All babies were tested in a supine position in a cot. The procedures for the recording and analysis of BAER, approved by the Children's Hospital Ethics Committee of Fudan University, were generally the same as those previously reported [9,10]. Briefly, 3 gold-plated disk electrodes were placed, respectively, on the middle forehead (positive), the ipsilateral earlobe (negative), and the contralateral earlobe (ground).…”
Section: Methodsmentioning
confidence: 99%
“…The analyses of BAER components, conducted blind to the medical history and clinical data of the subjects, were the same as previously described [9,10]. Measurements of 2 replicable BAER recordings to each stimulus condition were averaged for statistical analysis using SPSS version 20 (SPSS, Chicago, III., USA).…”
Section: Methodsmentioning
confidence: 99%